An applied study of patient perception for service quality in orthopedics clinics of public and private hospitals: A case study in Istanbul - Korkmaz, M., Kılıç, B., Yücel, A. S., Aksoy, M.,. (My University, 2014)
It is apparent that hospitals’ service quality is of utmost importance for the patients. The main objective of the study is to find out the patients’ public and private hospital preferences and the elements determining their preferences. Some differences concerning the increase in the patient satisfaction were observed in the study. The study examines whether the patients’ views on general quality level of orthopedics clinics differ according to some characteristics. In the study, measurement material is the questionnaire prepared for the patients in “Istanbul Private Maltepe Hospital”. Within the scope of the study, 250 questionnaires were distributed to the participants. The questionnaire, answered by randomly selected 169 patients, was considered suitable for the analysis. At the end of the reliability analysis, Cronbach’s coefficient about the basic data was found 0,928. At the end of the study, it has been observed that physicians, nurses, services and clinical factors have a profound impact on the patient satisfaction. It has been observed that the participants are highly satisfied with physician and nurse services, polyclinic hygiene, interest of personnel, treatment and care services. Most of the participants think positively for the hospital quality, and patients at orthopedics clinics also think positively. Further, it has been observed that the level of patients’ satisfaction differs according to demographical characteristics.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Health service; patient satisfaction; hospital and quality